A new ceramics approach for contact lens - Carpena DDS, MS, PhD, Guilherme; Ballarin DDS, Andressa; Aguiar, José (Odovtos - International Journal of Dental Sciences, 2015)
Nowadays the field of dentistry is focusing into a new aesthetic area in the light of an minimal invasive dentistry approach. Aesthetic treatments with dental porcelain veneers without any preparation (ceramic contact lenses) have gained popularity in recent years. Thus, the need for constant improvement and knowledge of innovative techniques and ceramics is fundamental. This article point out about the essential criteria to promote a clinical succeed of the technique over the years.